Finding Balance and Harmony: Modernity, Food, and the Partaking of the Holy Communion by Converts from Chinese Religious Traditions in Singapore - Benita Lim (Indonesian Journal of Theology, 2021)
As Christianity arrived on the shores of Singapore closely following British colonization, Western missionaries introduced their interpretation of the Holy Communion into a foreign land and space that was experiencing its first brushes with Western modernity. Contemporaneously, the movement of modernity continues to make an impact upon an important element of life closely intertwined with religious folk practices and culture of locals: food. In the face of modernizing foodscapes and primordial religious backgrounds, converts from Chinese religious traditions to Christianity find themselves navigating the dissonance of Western Holy Communion theologies with the Chinese philosophies of food. How might churches in Singapore begin to respond to the tensions arising when these two philosophical systems meet, and when Christians and churches seem to appropriate “syncretistic” theologies into their liturgical behavior? This article undertakes an interdisciplinary effort by employing social science to explore the modernizing of food in Singapore, as well as engaging Chinese philosophies of food and the body to explain tensions among converts from Chinese religious traditions, and the resistance of local churches towards Chinese understandings of food rituals in the partaking of the Holy Communion. It will also briefly propose that interdisciplinary studies, including liturgical studies, will be essential in developing a more robust theology of the Holy Communion among churches, thereby enhancing its witness within and without.